Radiological approach for early diagnosis of liver parenchymal disease - Rachna Chaurasia; Sunil (Asian Journal of Medical Sciences, 2024)
Background: Diffuse liver parenchymal disease (LPD) encompasses a wide range of liver disorders characterized by extensive involvement of liver tissue, often resulting in significant morbidity and mortality. Early detection and accurate assessment of these diseases are crucial for effective management and improved patient outcomes. Aims and Objectives: This study aims to evaluate the efficacy of various imaging modalities in the early detection and monitoring of diffuse LPDs, specifically focusing on non-invasive techniques such as ultrasonography (USG), computed tomography (CT), and Fibroscan. Materials and Methods: A prospective observational study was conducted involving 362 patients presenting with clinical signs and symptoms of liver disease at Maharani Laxmi Bai Medical College, Jhansi. Patients underwent standardized imaging protocols, including US, CT, and Fibroscan, along with laboratory tests to confirm liver function abnormalities. Imaging findings were correlated with clinical and laboratory data to assess diagnostic accuracy and efficacy. Results: The study found that ultrasound, elastography, and CT provide a reliable, non-invasive method for assessing diffuse LPD at the early stage ultrasound along with Fibroscan and CT both have comparable diagnostic capabilities in assessing diffuse LPD. Ultrasound and Fibroscan being non-invasive and radiation-free should be used as initial investigations whereas CT further contributes to the detailed characterization of liver parenchyma. Integration of these imaging modalities significantly enhanced early diagnosis and disease monitoring. Conclusion: Integrating advanced imaging modalities, especially elastography, into routine diagnostic protocols for diffuse LPDs enables early detection and effective management. Non-invasive techniques such as US and CT improve patient outcomes by allowing timely intervention and continuous monitoring of disease progression, thus reducing the need for invasive procedures such as liver biopsy.